Pengaruh Pemberian Tepung Deffated Larva BSF (Hermetia illucens) terhadap Performa Produksi Puyuh Petelur (Coturnix coturnix japonica) - S Mawaddah; W Hermana; N Nahrowi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2018)
High quality protein feedstuff prices for poultry are more expensive due to rising prices of imported raw materials, such as fish meal and meat bone meal (MBM). Utilization of an alternative source of protein that is abundant and does not compete with food needs, becomes one of the promising solutions to optimize production efficiency. This research will evaluate the potential utilization of black soldier fly (BSF) deffated larva mal as alternative source of MBM protein in quail feed on quail production performance by using method of decreasing fat (defatting) with emphasis (pressing). Female quail 5 weeks old as many as 285 birds. Quails devided in 3 treatments and 5 replications of each 19 tails. The experimental design used in this study was a complete randomized design (CRD). The feed applied was as follows: (P1) control feed, (P2) Feed with content 50% BSF (P3) feed with 100% BSF. The results of the study 50% and 100% subtitution of BSF deffated larva meal not significantly affected on egg production evidenced by no disruption of the production of eggs and raised 5.82% (P2) and 6.13% (P3) to feed control so that it can be concluded that deffated BSF meal alternative can be used as a substitute for MBM quail in feed. Keyword: Black soldier fly, deffated, quail, meat bone meal